2020
DOI: 10.21608/jappmu.2020.128930
|View full text |Cite
|
Sign up to set email alerts
|

Productive and Physiological Performance of Broilers Fed Diets Containing Different Levels of Olive Pulp

Abstract: This study was conducted to investigate the effect of using different levels of olive pulp in broiler diets on productive performance, carcass traits, protein fractions, lipids profile and antioxidant activity. One hundred eighty one-day old chicks were divided into four experimental groups (three replicates of 15 birds per treatment). Four experimental diets were used as follow: control, 5, 10, or 15% of olive pulp (OP) and fed up to five weeks of age. At 35 d of age, results showed that body weight and feed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 14 publications
6
12
0
Order By: Relevance
“…It is noted in the table a significant decrease in the cholesterol concentration in the blood plasma of birds for the treatments to which olive pomace was added, as for the decrease in the level of cholesterol in the blood plasma, it can be explained by the effect of zeptonol in increasing the level of Glutethione and Catalase proteins, and the activity of the enzyme Reductase-HMG-COA and as a result the decrease in the level of cholesterol, this was consistent with El-Baz et al [22], where these compounds work to reduce the absorption of cholesterol in the viscera and thus reduce its concentration in the blood, a decrease in the concentration of triglycerides (mg / 100 ml) in the blood of broilers was also observed for the treatments to which the bagasse was added, these results were in agreement with [16,23,24]. We conclude from the above that there is a clear positive effect of adding olive pomace to broiler diets on blood and tissue characteristics [25].…”
Section: Resultssupporting
confidence: 88%
“…It is noted in the table a significant decrease in the cholesterol concentration in the blood plasma of birds for the treatments to which olive pomace was added, as for the decrease in the level of cholesterol in the blood plasma, it can be explained by the effect of zeptonol in increasing the level of Glutethione and Catalase proteins, and the activity of the enzyme Reductase-HMG-COA and as a result the decrease in the level of cholesterol, this was consistent with El-Baz et al [22], where these compounds work to reduce the absorption of cholesterol in the viscera and thus reduce its concentration in the blood, a decrease in the concentration of triglycerides (mg / 100 ml) in the blood of broilers was also observed for the treatments to which the bagasse was added, these results were in agreement with [16,23,24]. We conclude from the above that there is a clear positive effect of adding olive pomace to broiler diets on blood and tissue characteristics [25].…”
Section: Resultssupporting
confidence: 88%
“…Total FI, final BWT and BWG showed nonsignificant decrease in birds fed 10 or 15% dietary OP compared to those fed 0 or 5% dietary OP (Table 7). The negative effect of high levels dietary OP on FI and FCR was noticed before by several authors as was found by ELbaz et al, (2020) who found that high levels of OP (10 and 15%) declined significantly the FCR compared with the control or 5% groups fed to Ross 308 broilers from 1 to 35 days of age. Moreover, FI decreased in group by 15%of OP compared to (0 or 5%) OP levels.…”
Section: Productive Performancesupporting
confidence: 60%
“…The effect of adding olive pulp to the feed in measuring some blood biochemical parameters of Awassi lambs (mean ± standard error). The reason for this decrease may also be due to the effect of the components of the bagasse, especially the effect of enzymes on the metabolism of carbohydrates through an increase in the activity of the glycogen syuthase enzyme, reducing the activity of glycogen phosphorylate enzyme [10]. Where these compounds work to reduce the absorption of cholesterol in the body and thus lower its concentration in the blood.…”
Section: Resultsmentioning
confidence: 99%